GLUCOSE AND HEART RATE ANSWERS OF A PARACHUTE JUMP AND COMPARISON BETWEEN EXPERIENCED AND NOVICES (Fiep Bulletin - online, 2014)
Abstract: The present research is a comparative and descriptive study that's intended to compare Heart Rate (HR) and glucose on sky divers with over 4100 jumps and first time sky dive students. Instrument: Glucose were measured before the jump and 3 and 5 minutes after landing. HR was measured through the whole period, beginning from 4 minutes before the departure, until the 10th minute after landing. The Student test T was used on independent data to verify the level of significancy in between both groups. With this, we intend to discuss the interferences in sky diving in these variables. Results shows an increase in all variables in first time sky dive students, with the exception of landing. If analyzed by percentage, the experience group shows higher results. HR levels are also similar during all moments but at the end of the jump.
Keywords: Sky dive; Heart Rate; Glucose